HUBUNGAN KESEGARAN JASMANI DENGAN HASIL BELAJAR PENJASORKES KELAS VII PUTRA SMP METHODIST PEKANBARU TAHUN AJARAN 2015/2016 - Sitohang, Andri Prasetya Elizer; ', Saripin; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problems of the research based on the researcher’s observation was the activeless students and low physical fitness which could be observed from students’ low study spirit theoritically and practically. The result of students in studying was 60% of thirty students passing the minimum score standard ( Keriteria Ketuntasan Minimal ) which was 80 points.This research was conducted to know that there was correlation of physical fitness through the seventh grade students’ learning outcomes in sport lesson of SMP Methodist Pekanbaru 2015 / 2016. The sample of this research was thirty three students of seventh grade of SMP Methodist Pekanbaru 2015 / 2016. The technique of collecting data was total sampling and the instruments of this research were 50 meter – run, sixty – second – body lifting, sixty – second – lying, three – time vertical jump, and 1000 – metre middle distance run. Then, the data were treated statistically to examine nomality by liliefors in standard of significant 0.05. The hypothesis was proposed that there was a significant correlation between physical fitness and the students’ learning outcome at seventh grade of SMP Methodist Pekanbaru 2015 / 2016. According to the analysis of Liliefors test, it resulted Lcount (x) was 0.123 and Ltable was 0.154. Lcount (y) was 0.088 and Ltable was 0.154. It meant that Lcount< Ltable, so the samplewas from normal distributive population. Then, the result of product moment between the physical fitness and students’ learning outcome was rcount 0.407 and rtable 0.349. It meant that rcount > rtable which was Ha accepted and Ho refused.Based on the research result, there was the correlation of physical fitness through the seventh grade students’ learning outcomes in sport lesson of SMP Methodist Pekanbaru 2015 / 2016.Keywords : Physical fitness, students’ learning outcome